The Migration–Development Nexus Revisited: A Place‐based Mobility Perspective from the Borderlands - Kaşlı, Zeynep; Winters, Nanneke (Development and change, 2025)
Migration, a fundamental characteristic of planetary life and human livelihood, has been considered a key driver of development. However, as identified by critical migration and mobility scholars, the assumed positive relationship to development has been predominantly informed by a neoliberal, managerial and sedentary view of migration. Tackling such highly instrumental and uni‐directional approaches to migration, which still inform policy and scholarly debates on the so‐called migration–development nexus, this article argues that the accomplishments in migration scholarship which recognize the volatility and violence of migrant trajectories and the transformation of border communities are insufficiently taken up in dominant migration–development thinking. Based on ethnographic research in two borderlands in Central America and the Eastern Mediterranean, the authors propose a place‐based mobility perspective to historicize and ‘de‐migranticize’ lived experiences of (im)mobility to enrich migration–development thinking. To achieve this, they advocate an approach that considers multiple scales and populations simultaneously, enabling a better understanding of the socio‐economic, political and environmental effects of (im)mobilities in the lives of both migrants and residents. This place‐based mobility perspective contributes to a more nuanced understanding of human mobility in development studies, and a way forward for a more critical approach to ‘development’ in migration scholarship.